2021
DOI: 10.1088/1755-1315/936/1/012038
|View full text |Cite
|
Sign up to set email alerts
|

A Long-term Spatial and Temporal Analysis of NDVI Changes in Java Island Using Google Earth Engine

Abstract: Java is Indonesia’s and the world’s most populous island. The increase in population on the island of Java reduces the area of forest and other vegetation covers. Landslides, floods, and other natural disasters are caused by reduced vegetation cover. Furthermore, it has the potential to lead to the extinction of flora and fauna. The Normalized Difference Vegetation Index (NDVI) can be used to monitor the vegetation cover. This study analyzes the NDVI changes value from 2005 to 2020 using Terra and Aqua MODIS i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Analyses of previous studies demonstrated that there was a similar performance of MODIS and Landsat data [69], [70]. Therefore, we can use the low spatial resolution MODIS data to study relationships between NDVI and climate factors [71].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Analyses of previous studies demonstrated that there was a similar performance of MODIS and Landsat data [69], [70]. Therefore, we can use the low spatial resolution MODIS data to study relationships between NDVI and climate factors [71].…”
Section: Introductionmentioning
confidence: 86%
“…The goal of this research was to study the time-lag effects of the vegetation responses to climate variables in the mountain grassland ecosystems during 1984-2018 using MODIS-, Landsat-derived NDVI data with BRDF, topographic and atmospheric corrections applied, temperature and precipitation data from meteorological stations and Google Earth Engine (GEE) cloud platform [122]. GEE is a cloud-based geospatial analysis platform for scientific analysis and visualization of geospatial datasets; it enables processing of satellite imagery to detect changes, which has been widely used in similar studies in recent years [37], [71], [123].…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of previous studies demonstrated that there was a similar performance of MODIS and LANDSAT data [59,64,67,68]. Therefore, we can use the low spatial resolution MODIS data to study relationships between NDVI and climate factors [69].…”
Section: Introductionmentioning
confidence: 87%
“…The goal of this research was to study the time-lag effects of the vegetation responses to climate variables in the mountain grassland ecosystems during 1984-2018 using MODISand LANDSAT-derived NDVI data with BRDF, with topographic and atmospheric corrections applied, and temperature and precipitation data from meteorological stations and the Google Earth Engine (GEE) cloud platform [122]. GEE is a cloud-based geospatial analysis platform for scientific analysis and visualization of geospatial datasets; it enables processing of satellite imagery to detect changes, which has been widely used in similar studies in recent years [34,69,123].…”
Section: Introductionmentioning
confidence: 99%
“…From 2009-2011, deforestation in Java consisted of 500 Ha of conservation forest, 800 Ha of protected forest, 4,100 Ha of limited production forest, and 3,500 Ha of production forest. From the side of NDVI, Java is getting down the NDVI year by year with a -0.00047 rate [10].…”
Section: Introductionmentioning
confidence: 99%